Is AJCC/UICC Staging Still Appropriate for Head and Neck Cancers in Developing Countries?. Issue 3 (July 2020) - Fagan, Johannes J.; Wetter, Julie; Otiti, Jeffrey; Aswani, Joyce; Konney, Anna; Diom, Evelyne; Baidoo, Kenneth; Onakoya, Paul; Mugabo, Rajab; Noah, Patrick; Mashamba, Victor; Kundiona, Innocent; et al.
By 2030, 70% of cancers will occur in developing countries. Head and neck cancers are primarily a developing world disease. While anatomical location and the extent of cancers are central to defining prognosis and staging, the American Joint Committee on Cancer (AJCC)/International Union Against Cancer (UICC) have incorporated nonanatomic factors that correlate with prognosis into staging (eg, p16 status of oropharyngeal cancers). However, 16 of 17 head and neck surgeons from 13 African countries cannot routinely test for p16 status and hence can no longer apply AJCC/UICC staging to oropharyngeal cancer. While the AJCC/UICC should continue to refine staging that best reflects treatment outcomes and prognosis by incorporating new nonanatomical factors, they should also retain and refine anatomically based staging to serve the needs of clinicians and their patients in resource-constrained settings. Not to do so would diminish their global relevance and in so doing also disadvantage most of the world's cancer patients.